(untitled) (International conference on multidisciplinary science, 2023)
This article provides practical strategies and insights on fostering a creative teaching atmosphere in the classroom. It explores the importance of creating an environment that encourages curiosity, exploration, and innovative thinking among students. Drawing on research and real-world examples, the author discusses various techniques such as incorporating hands-on activities, promoting open-ended discussions, and integrating technology to engage students’ creativity. The article also highlights the role of the teacher in facilitating a supportive and encouraging atmosphere that nurtures students’ creative potential. By offering concrete suggestions and emphasizing the benefits of a creative teaching atmosphere, this article serves as a valuable resource for educators seeking to enhance student creativity and foster a dynamic learning environment.